Pengaruh Penyikatan Dengan Pasta Gigi Terhadap Kekasaran Permukaan Nano-ionomer Dan Semen Ionomer Kaca Modifikasi Resin - Ellyza Herda; Anna Fitri Fawzia; Andi Soufyan (Ikatan Peminat Ilmu Material dan Alat Kedokteran Gigi (IPAMAGI), 2012)
The implementation of nano technology on resin modified glass ionomer cement (RMGIC) results in the latest restorative material which is known as Nano-ionomer. The surface texture of the restoration is one of the most important factors that influences the successful of the material usage. Surface irregularity may cause plaque retention, surface discoloration, and gingival irritation. Objective: To analyze the effect of brushing with toothpastes to the surface roughness of Nano-ionomer and RMGIC. Specimens of Nano-ionomer and RMGIC are brushed with distilled water, anti-cavity toothpaste, and whitening toothpaste (6 Specimens each) for 60 minutes, every 10 minutes the surface roughness are measured with Surface Roughness Tester (Ra). The data are statistically analyzed using Paired-samples t-Test, One-way ANOVA, and Independent-samples t-Test. There is an increase in the surface roughness of both group samples after brushing. As for RMGIC, there is a significant difference between the surface roughness values after brushing with distilled water, anti-cavity toothpaste, and whitening toothpaste, while for Nano-ionomer, the difference is not significant. Once compared, there is a significant difference between the surface roughness increase of RMGIC and Nano-ionomer (p<0.05) which can be seen after brushing for 60 minutes. The increase of surface roughness of RMGIC is significantly higher than Nano-ionomer.